What Causes Anxiety in Emerging Adulthood? : A Sytematic Review (International Journal of Scientific Research and Management (IJSRM), 2024)
Emerging adulthood is the transition phase from adolescence to adulthood, starting from the age of 18-29 years. At this age, many individuals experience anxiety caused by past experiences. Existing anxiety can affect an individual’s mood, thoughts and behavior. This systematic review examines 14 international journals selected from the Scopus database regarding factors causing anxiety in emerging adulthood. If individuals in this phase know the factors that influence anxiety, they can take preventive action to avoid anxiety occurring in themselves. The results found that factors causing anxiety in emerging adulthood include: self-esteem, parenting patterns and bad experiences as children. These findings provide recommendations for conducting further and specific systematic review research and are expected to be a consideration for preventive actions before and during the emerging adulthood phase.